Insulin Secretion in Cardiogenic Shock - Dykes, J. R. W. (1969)
A nearly complete suppression of insulin secretion was observed in four patients in circulatory shock following acute myocardial infarction. This may be due to intense sympathetic activity and raised catecholamine excretion associated with shock.